Design and fabrication of portable laser cutting and engraving machine - Jamaleswara Kumar, P.; Siva Sai Tarun, A.; Gowtham, M.; Thamma Rao, P.; Yashwanth, G. (International Journal of Engineering and Technology, 2017)
Now a days digital control technology is became more and more useful to run the machines like portable laser cutting and engraving machines that can cut on the different surface contingent upon the power of the laser diode. In this paper the fundamental goal is to design and fabricate the laser cutting and engraving machine which is convenient to controlled by the Arduino CNC. It is accessible and perfect utilization for small and medium scale industries. This model is small, simple to work, cost of manufacturing and to effortlessly transport from one work station to other work station.
Keywords: Laser Module; Arduino; Stepper Motor; Eleksmaker.